2009
DOI: 10.1364/oe.17.012523
|View full text |Cite
|
Sign up to set email alerts
|

Thermal regeneration of fiber Bragg gratings in photosensitive fibers

Abstract: We report about a thermal regeneration of fiber Bragg gratings written in photosensitive fibers with nanosecond laser pulses. We observe a regenerative process in a highly photosensitive fiber without hydrogen loading which indicates a secondary grating growth in an optical fiber by thermal activation. This process is more temperature stable than the commonly known gratings produced by color center modifications. The writing conditions of such new type of gratings are investigated and the temperature behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…Since our work, others [Linder et al 2009] have shown that regeneration can be obtained at lower temperatures in gratings written without hydrogen -the low thermal stability of these gratings is consistent with type 1n gratings. If crystallisation is occurring it is likely to be via the mechanism we described above to α−quartz, which is stable at ~100Mpa close to the observed 600°C.…”
Section: Regenerationsupporting
confidence: 79%
See 2 more Smart Citations
“…Since our work, others [Linder et al 2009] have shown that regeneration can be obtained at lower temperatures in gratings written without hydrogen -the low thermal stability of these gratings is consistent with type 1n gratings. If crystallisation is occurring it is likely to be via the mechanism we described above to α−quartz, which is stable at ~100Mpa close to the observed 600°C.…”
Section: Regenerationsupporting
confidence: 79%
“…The use of hydrogen was important, but not necessarily essential, to obtain index modulation of useful magnitude for very high temperature operation, since it permitted enhanced localisation of the pressure differences between processed and unprocessed regions. The model proposed in Canning et al 2008b is independent of this and recent work demonstrates that regeneration can be achieved without hydrogen, although for much lower temperature operation [Linder et al 2009]. In this chapter, we briefly review the hypothesis and demonstrate thermal processing of UV-induced templates that retain the nano-scale precision of the template whilst stabilising the glass change to unprecedented levels.…”
Section: Historical Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…A spatially-dependent refractive index can be imprinted in the fiber by modulating the intensity pattern of the writing laser. Lindner et al (2009) use a Talbot interferometer to create a periodic modulation of the refractive index in a Bragg mirror configuration. Two Bragg reflectors produce an 3 counts per second (cps), and the measurement background noise including the dark count is about 10 kcps.…”
Section: Bragg Resonatorsmentioning
confidence: 99%
“…For high temperature applications, two competing FBG technologies exist: 1) regenerated gratings resulting from high temperature annealing of strong type I laser written gratings in hydrogen loaded fiber [3,4] and 2) type II gratings written with femtosecond pulse duration radiation, either using the point-by-point method [5] or using the phase mask approach [6]. Regenerated gratings typically possess low reflectivity and are cumbersome to produce, requiring high temperature processing in an oxygen free environment and, usually high pressure hydrogen loading of the optical fiber at some point in the process [7].…”
Section: Introductionmentioning
confidence: 99%